2014
DOI: 10.1016/j.ehb.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Examining the temporal relationships between childhood obesity and asthma

Abstract: Childhood obesity has become an issue of increasing concern to health researchers and policymakers in the United States. One important chronic health condition linked to obesity is pediatric asthma. Although researchers have speculated that both conditions may have common origins, the majority of research in this area has focused on a unidirectional relationship between obesity and later asthma. However, much of the literature is limited by its reliance on cross-sectional data and its failure to examine the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 40 publications
2
32
0
1
Order By: Relevance
“…Willeboordse et al also did not find any relationship between asthma, Body Mass Index or the association of these two parameters and differences in physical activity [19]. The statements made by Green [7] are corroborated by Hossain et al that describes that children show an increase in the rate of weight gain after the diagnosis of asthma adding that this increase was steeper in females and African-Americans and Hispanics [20]. Ahmadiafshar et al also found that asthmatic children were more likely to have a higher BMI than their non-asthmatic counterparts [21].…”
Section: Obesity Indicators Relation With Asthmamentioning
confidence: 76%
See 3 more Smart Citations
“…Willeboordse et al also did not find any relationship between asthma, Body Mass Index or the association of these two parameters and differences in physical activity [19]. The statements made by Green [7] are corroborated by Hossain et al that describes that children show an increase in the rate of weight gain after the diagnosis of asthma adding that this increase was steeper in females and African-Americans and Hispanics [20]. Ahmadiafshar et al also found that asthmatic children were more likely to have a higher BMI than their non-asthmatic counterparts [21].…”
Section: Obesity Indicators Relation With Asthmamentioning
confidence: 76%
“…Despite most research focusing on the unilateral relationship between obesity and later asthma, past asthma is positively linked with changes in Body Mass Index and the onset of obesity according to Green [7]. However, it is important to note that only new onset asthma is correlated with subsequent changes in BMI [7].…”
Section: Obesity Indicators Relation With Asthmamentioning
confidence: 93%
See 2 more Smart Citations
“…A bidirectional association between asthma and obesity is biologically plausible since many children with asthma avoid exercise [16-18], increase sedentary time[19], and receive treatment with oral corticosteroid medications – three factors which promote weight gain. Several investigators have now shown greater subsequent weight gain among asthmatics compared to non-asthmatics [20, 21]. Reduced activity in asthmatic children is not universal, and appears to depend on the attitudes and teaching of parents about the role of exercise in asthma control [16, 18-20, 22-24], and may also be affected by childhood emotional health[18, 24].…”
Section: Origins Of Pediatric Obese Asthmamentioning
confidence: 99%